THE PROJECT "POLSKA DLA BIBLIOTEKARZY": ON THE ROAD TO EUROPEAN INTEGRATION - Stepaniuk, Olena L (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article is dedicated to collaboration of libraries of different forms of subordination. The author examines intersectoral links between the public library (the Dnipro Central City Library) and scientific libraries of some institutions of higher education, namely the participation of 16 librarians in the project “Polska dla bibliotekarzy”. The project aims to teach participants to use Polish effectively for everyday and professional communication, which should expand opportunities for professional growth and establishment of international business and cultural ties.